Pesantren dan Pembentukan Jalan Hidup Kaum Sufi Urban - Muhammad Masyhuri (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2017)
This paper explains how the adherents of urban tarekat form sufism that becomes a way of life in their daily life. This study is considered important because the existence of tarekat adherents is often positioned as part of traditional society, which is contrary to aspects of modernity. On the contrary, their current existence is not only widely embraced by the urban community, but also a way of life in responding to modernity. Related to that, the following describes the process of forming the path of life of the three congregation adherents of tarekat communities such as Raden Rahmad Pesantren and Surau Ghautsil Amin in Jember District. Using ethnographic methods that attempt to explain how they learn to live in conjunction, this study will formulate how they seek to renew tradition to modernity, and how they attempt to explain how modernity and tradition are an integral part of one another